2022
DOI: 10.3390/ijms23042345
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Insight into the Interaction of Metal-Decorated Fluorinated Carbon Fullerenes with Anti-COVID Drugs

Abstract: We theoretically investigated the adsorption of two common anti-COVID drugs, favipiravir and chloroquine, on fluorinated C60 fullerene, decorated with metal ions Cr3+, Fe2+, Fe3+, Ni2+. We focused on the effect of fluoridation on the interaction of fullerene with metal ions and drugs in an aqueous solution. We considered three model systems, C60, C60F2 and C60F48, and represented pristine, low-fluorinated and high-fluorinated fullerenes, respectively. Adsorption energies, deformation of fullerene and drug mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Lower surface coverage levels could achieve comparable doping effects. [160] Ab initio calculations indicated that Ni-doped C 60 F 48 could provide carriers for anti-covid drugs such as chloroquine, [161] a drug that, unfortunately, proved ineffective against covid.…”
Section: Highly Fluorinated Carbon Allotropesmentioning
confidence: 99%
“…Lower surface coverage levels could achieve comparable doping effects. [160] Ab initio calculations indicated that Ni-doped C 60 F 48 could provide carriers for anti-covid drugs such as chloroquine, [161] a drug that, unfortunately, proved ineffective against covid.…”
Section: Highly Fluorinated Carbon Allotropesmentioning
confidence: 99%
“…Reaching a therapeutic outcome that is able to fight neurodegenerative disorders, tumoral diseases, or immunological disorders is facilitated by an efficient and site-specific delivery of compounds. For these reasons, this Special Issue collates different aspects of research into nanotechnology in order to identify new therapeutic targets and strategies, including review papers [4,5], mathematical models to calculate the trajectories of magnetic NPs in the body or clarify the structures of metal-decorated fullerenes [6,7], the drug delivery systems of different antitumoral agents [8][9][10][11], and the biocompatibilities of stealth liposomes and hybrid nanosystems containing surfactant agents [12,13].…”
mentioning
confidence: 99%